Yogic Traditions of India and their Educational Implications with Reference to Development of Values - Lakshmi, R. K. Roshni Raj (JOURNAL OF INDIAN EDUCATION, 2021)
Values are the set of beliefs that an individual or a community believes in. Values help to establish a just society. Value education is the kind of education, which helps to inculcate certain positive values in children. The introduction of value education in Indian education system started with the Radhakrishnan Commission. It is accepted worldwide that value education is the need of the hour. Even UNESCO has advised that education should have value education as a component. Yoga philosophy is one of the six Indian philosophies. It teaches the ideal way of life and purpose of life. It espouses inculcation of constructive values throughout the journey of yoga. Thus, it can be concluded that yoga has a major contribution to make in the cultivation of values in an individual. It implies that including yoga in the curriculum will ensure values to be internalised in children.